STUSTAINABLE DEVELOPMENT GOALS (SDGs) IN THE PERSPECTIVE OF DAKWAH AND COMMUNITY DEVELOPMENT - Irwandi, Irwandi; Karni, Awis; Sulastri, Irta; Nazirman, Nazirman (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
The purpose of writing this article is to look at the role of Islam in overcoming poverty through a global program initiated by the United Nations (UN) through the Sustainable Development Goals (SDGs) program or sustainable development goals, one of which is the problem of poverty (no poverty). This research is a qualitative descriptive research using library research methods. This is relevant to achieving the aim of this research, namely exploring sustainable development from the perspective of preaching community empowerment. In this research, the concepts and theories used will be evaluated based on existing literature, especially research results in the form of the Al-Quran, Hadith, textbooks and other relevant materials regarding the 17 main goals of the Sustainable Development Goals (SDGs). The research results show that Islam has laid the main foundations in building society to overcome poverty and local wisdom culture, especially in Minangkabau, plays a very important role in overcoming poverty.